1990
DOI: 10.1042/bj2700305
|View full text |Cite
|
Sign up to set email alerts
|

Detergent solubilization of phospholipid vesicle. Effect of electric charge

Abstract: In order to explore the effect of electric charge on detergent solubilization of phospholipid bilayers, the interaction of nine electrically charged surfactants with neutral or electrically charged liposomes has been examined. The detergents belonged to the alkyl pyridinium, alkyl trimethylammonium or alkyl sulphate families. Large unilamellar liposomes formed by egg phosphatidylcholine plus or minus stearylamine or dicetyl phosphate were used. Solubilization was assessed as a decrease in light-scattering of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 16 publications
7
72
0
1
Order By: Relevance
“…Recently, many important phenomena affecting lipid bilayers, including their detergent solubilization, have been explored by using liposomes; such studies promote a better understanding of the biophysical properties of bilayer membranes and moreover will improve the handling of membrane proteins when they are isolated from or reconstructed into lipid bilayers (10)(11)(12)(13). However, studies of intermediate stages in the detergent solubilization of liposomes are only now in progress (14)(15)(16)(17), and the interaction mechanism between membranes and surfactants has remained unclear. Therefore, real-time approaches by using optical microscopy to study the dynamic behavior of liposomes are very important.…”
mentioning
confidence: 99%
“…Recently, many important phenomena affecting lipid bilayers, including their detergent solubilization, have been explored by using liposomes; such studies promote a better understanding of the biophysical properties of bilayer membranes and moreover will improve the handling of membrane proteins when they are isolated from or reconstructed into lipid bilayers (10)(11)(12)(13). However, studies of intermediate stages in the detergent solubilization of liposomes are only now in progress (14)(15)(16)(17), and the interaction mechanism between membranes and surfactants has remained unclear. Therefore, real-time approaches by using optical microscopy to study the dynamic behavior of liposomes are very important.…”
mentioning
confidence: 99%
“…The solubilization of liposomes was greatly influenced by HLB, whereas it was minorly influenced by electrostatic forces. Another study by M. Angeles Urbaneja et al had shown that the solubilization of liposomes by alkylpyridinium micelles do not largely depends upon electrostatic forces but is chiefly influenced by hydrophobic interactions 45) . Solubilization of water in organic solvents has also been achieved by pyridinium surfactants.…”
Section: Quaternary Pyridinium Salts: a Reviewmentioning
confidence: 99%
“…In accordance with the procedure described by Urbaneja et al (1990) and Ruiz et al (1994) the solubilizing interaction of SC with PC liposomes was studied through the changes in the static light-scattering 24 h after the addition of surfactant with a reading angle of 90Њ. Figure 1 shows the solubilization curve for a liposome suspension (PC concentration 5 .…”
Section: Tem Observations Quasielastic and Static Light-scattering Vmentioning
confidence: 99%
“…It has been previously demonstrated that static light scattering (SLS) constituted a very convenient technique for the quantitative study of liposome solubilization by different surfactants (Urbaneja et al, 1990;Inoue et al, 1992;Ruiz et al, 1994). Accordingly, the solubilizing perturbation produced by the SC in PC liposomes was monitored using this technique.…”
Section: Solubilization Of Liposomesmentioning
confidence: 99%
See 1 more Smart Citation